Uberlandszaft bólu oczu. Wanna z kolumnadą. Reportaże o polskiej przestrzeni (2020) Filipa Springera - Bloch, Irmina (Przestrzenie Teorii, 2025)
The author discusses the second edition of Filip Springer’s collection of reportage-essays Wanna z kolumnadą. Reportaże o polskiej przestrzeni [Bathtub with a colonnade. Reportages on Polish space] from the perspective of the poetics of photographic experience. Springer’s work (the author of Miedzianka) is often reduced to the statement that he points out the paradoxes of space. However, in the case of Wanna z kolumnadą, the landscape turns out to be a multi-level, palimpsest experience, discovered and described by means of photographs and statistics, legal texts and residents’ accounts. As a result, space becomes not so much an object of analysis, but rather evidence in a case against Polish law and Polish reality.